New insight into the structure and function of Hfq C-terminus. Issue 2 (28th April 2015) - Fortas, Emilie; Piccirilli, Federica; Malabirade, Antoine; Militello, Valeria; Trépout, Sylvain; Marco, Sergio; Taghbalout, Aziz; Arluison, Véronique
Abstract : We showed that Hfq C-terminal region (CTR) has an intrinsic property to self-assemble into amyloid-like fibrils. This region is required for cellular assembly of Hfq into membrane-associated coiled structures. The work establishes a new function for this naturally unstructured Hfq domain. Abstract : Accumulating evidence indicates that RNA metabolism components assemble into supramolecular cellular structures to mediate functional compartmentalization within the cytoplasmic membrane of the bacterial cell. This cellular compartmentalization could play important roles in the processes of RNA degradation and maturation. These components include Hfq, the RNA chaperone protein, which is involved in the post-transcriptional control of protein synthesis mainly by the virtue of its interactions with several small regulatory ncRNAs (sRNA). The Escherichia coli Hfq is structurally organized into two domains. An N-terminal domain that folds as strongly bent β-sheets within individual protomers to assemble into a typical toroidal hexameric ring. A C-terminal flexible domain that encompasses approximately one-third of the protein seems intrinsically unstructured. RNA-binding function of Hfq mainly lies within its N-terminal core, whereas the function of the flexible domain remains controversial and largely unknown. In the present study, we demonstrate that the Hfq-C-terminal region (CTR) has an intrinsic property to self-assemble into long amyloid-like fibrillar structures in vitro . We show that normal localization of Hfq within membrane-associated coiled structures in vivo requires this C-terminal domain. This finding establishes for the first time a function for the hitherto puzzling CTR, with a plausible central role in RNA transactions.